2005
DOI: 10.1002/jccs.200500001
|View full text |Cite
|
Sign up to set email alerts
|

Application of Liquid Crystalline NMR Solvents to a Mixture of Ketones

Abstract: A series of dilute liquid crystalline solvents are used to study the effect of slight anisotropy caused by partial alignment on chemical shift and residual dipolar coupling (RDC) in small molecules. The residual dipolar couplings between protons in solutes are found to be almost independent of the local environment. It is also found that the chemical shift does not change over the concentration range observed. A linear relationship between residual dipolar coupling and liquid crystal concentration is observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Dilute liquid crystal solvents at different concentrations have been used to study the effect of partial alignment on chemical shift and residual dipolar couplings in small molecules. 133 It is observed that the chemical shift does not change over the concentration range studied while residual dipolar couplings exhibit a linear relationship at relatively low concentrations. A swollen lamellar phase based on sodium dodecyl sulfate, pentanol and NaBr brine, has been examined by means of NMR spectroscopy of quadrupolar nuclei, namely 2 H, 17 O, 23 Na and 81 Br, present at natural abundance.…”
Section: Structure and Orientation Of Small Moleculesmentioning
confidence: 85%
“…Dilute liquid crystal solvents at different concentrations have been used to study the effect of partial alignment on chemical shift and residual dipolar couplings in small molecules. 133 It is observed that the chemical shift does not change over the concentration range studied while residual dipolar couplings exhibit a linear relationship at relatively low concentrations. A swollen lamellar phase based on sodium dodecyl sulfate, pentanol and NaBr brine, has been examined by means of NMR spectroscopy of quadrupolar nuclei, namely 2 H, 17 O, 23 Na and 81 Br, present at natural abundance.…”
Section: Structure and Orientation Of Small Moleculesmentioning
confidence: 85%